2014
DOI: 10.1371/journal.pone.0094803
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Withania somnifera Leaf Transcriptome and Expression Analysis of Pathogenesis – Related Genes during Salicylic Acid Signaling

Abstract: Withania somnifera (L.) Dunal is a valued medicinal plant with pharmaceutical applications. The present study was undertaken to analyze the salicylic acid induced leaf transcriptome of W. somnifera. A total of 45.6 million reads were generated and the de novo assembly yielded 73,523 transcript contig with average transcript contig length of 1620 bp. A total of 71,062 transcripts were annotated and 53,424 of them were assigned GO terms. Mapping of transcript contigs to biological pathways revealed presence of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 150 publications
1
20
0
Order By: Relevance
“…In our current study, we generated a total of 249 million high-quality reads from in vitro -grown leaf and root tissues, more than the previously reported ESTs and transcriptome data [ 20 , 30 , 31 ]. We obtained a total transcriptome size of 183 Mbps with average transcript length of 1,033 bp (Table 1 ) which is comparatively better than a previous Withania 454 transcriptome study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our current study, we generated a total of 249 million high-quality reads from in vitro -grown leaf and root tissues, more than the previously reported ESTs and transcriptome data [ 20 , 30 , 31 ]. We obtained a total transcriptome size of 183 Mbps with average transcript length of 1,033 bp (Table 1 ) which is comparatively better than a previous Withania 454 transcriptome study [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the phenylpropanoid biosynthesis pathway was found to harbour the largest cluster of transcripts. In a recent study, Dasgupta et al [ 31 ] reported 184 pathways from their in vitro leaf transcriptome library. The additional pathways may be due to pathogenesis-related genes expressed in response to salicylic acid signalling in the source tissue of their study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of this hormone results in a delay in the activation of genes involved in the defense response (Baebler et al, 2014). The effect of salicylic acid results in an increase in the activity of pathogenesis related (PR) gene fam ilies (except PR10) and in the increased accumulation of secondary metabolites (that have antitumor and bacteriostatic effects) in the Withania somnifera L. medicinal plant (Ghosh Dasgupta et al, 2014). Phy topathogens induce a disturbance in the level of hor mone balance in plants rearranging the host transcrip tome work to its own advantage.…”
Section: Introductionmentioning
confidence: 99%
“…It is a dicotyledonous plant of the family Solanaceae and widely used in traditional medical systems of India and Africa as adaptogens (physical and mental health promoter) or vitalizers (Dasgupta et al 2014). …”
Section: Introductionmentioning
confidence: 99%